Global value chains: a view from the euro area - Jo\~ao Amador; Rita Cappariello; Robert Stehrer (European Central Bank (ECB), 2015)
This paper describes the main features of Global Value Chains (GVCs) in the euro area taken as a whole and compares with other large trade players like the US, China and Japan. In addition, the perspective of individual euro area countries is considered, with a focus on intra euro area linkages. The analysis relies primarily on the concept of foreign value added in exports, as a way to assess the pervasiveness of GVCs, it covers the period 2000-2011 and bases on the World Input-Output Database (WIOD). The paper finds that GVCs are important for the euro area as whole and they have rebounded after the great trade collapse. Moreover, there is a strong relevance of regional production linkages in Europe, with Germany playing a key role.
Keywords: F1; F14; F15; 330; euro area; global value chains; International trade